The Influence of Work Environment and Work Motivation on Employee Performance at Boawae Credit Cooperative, Nagekeo Regency (Jurnal Ekonomi Pembangunan Widya Mandira, 2026)
This study aims to analyze the effect of the work environment and work motivation on employee performance at the Boawae Credit Cooperative, Nagekeo Regency. The study employed a quantitative approach with an associative method. The population consisted of 116 employees, with a sample of 54 respondents determined through simple random sampling using the Slovin formula. Data were collected through a Likert-scale questionnaire and analyzed using simple linear regression, multiple linear regression, and classical assumption tests with the assistance of SPSS version 25. The results indicate that a good work environment, such as comfortable conditions, harmonious relationships, and adequate facilities, has a significant effect on improving employee performance. In addition, high work motivation, reflected in enthusiasm, responsibility, and the drive to achieve targets, also enhances performance. Simultaneously, a conducive work environment and high motivation reinforce each other in improving employee performance. These findings emphasize the importance of improving the work environment and increasing motivation as management efforts to enhance employee performance
Keywords: Work Environment; Work Motivation; Performance; Credit Cooperative; Boawae Cooperative